1995
DOI: 10.1002/app.1995.070550203
|View full text |Cite
|
Sign up to set email alerts
|

Low loss second‐order nonlinear optical polymers based on all organic sol‐gel materials

Abstract: A new class of all organic sol‐gel second‐order nonlinear optical (NLO) materials based on hexa(methoxymethyl) melamine (HMM) was developed. Two NLO active chromophores, 4 (4′‐nitrophenylazo) aniline (DO3) and 4‐amino‐4′‐nitrobiphenyl (ANB), were incorporated into the melamine matrices. The samples exhibited second‐order optical nonlinearity after poling and curing at 220°C for 30 min. DO3/HMM and ANB/HMM samples showed a second harmonic coefficient, d33 of 10.7 and 1.8 pm/V at 1064 nm, respectively. The tempo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

1998
1998
2009
2009

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 21 publications
0
16
0
Order By: Relevance
“…The sample was then cooled down to room temperature in the presence of the poling field at which point the poling field was terminated. Optical losses of the polymer waveguides for poly(amide-imide)-clay nanocomposites were measured according to the literature [32]. The laser beam (830 and 1310 nm) first passes through a linear polarizer and a polarizing beam splitter, thus removing noise caused by polarizing fluctuations in the laser output.…”
Section: Poling Process Eo Coefficient (R 33 ) and Optical Loss Measmentioning
confidence: 99%
“…The sample was then cooled down to room temperature in the presence of the poling field at which point the poling field was terminated. Optical losses of the polymer waveguides for poly(amide-imide)-clay nanocomposites were measured according to the literature [32]. The laser beam (830 and 1310 nm) first passes through a linear polarizer and a polarizing beam splitter, thus removing noise caused by polarizing fluctuations in the laser output.…”
Section: Poling Process Eo Coefficient (R 33 ) and Optical Loss Measmentioning
confidence: 99%
“…In addition, melamine-based polymers can show low optical loss and high T g . Jeng et al 6 and Hsiue et al 7 reported that methylated hexamethylolmelamine (HMM) was used for preparing NLO polymer materials.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, melamine-based polymer could show low optical loss and high Tg. Some literature (11,12) reported that methylated hexamethylolmelamine was taken for preparing NLO polymer materials.…”
Section: Introductionmentioning
confidence: 99%